Gunpowder, Masculinity, and Warfare in German Texts, 1400-1700 - Brugh, Patrick (Book collections on Project MUSE., 2019)
How gunpowder technology exploded heroes, heroics, and war stories from 1400 to 1700, and how German writers tried to glue them back together.